PENGETAHUAN, SIKAP DAN PERILAKU PEMBERANTASAN SARANG NYAMUK TERHADAP INFEKSI DENGUE DI KECAMATAN DENPASAR SELATAN, KOTA DENPASAR, BALI - Sang Gede Purnama; Tri Baskoro Satoto; Yayi Prabandari (Program Studi Sarjana Kesehatan Masyarakat Universitas Udayana Berasosiasi Dengan Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI), 2013)
Dengue hemorrhagic fever (DHF) is a global health problem. Denpasar city is one of endemicareas in Bali Province. Based on Bali Provincial Health Offi ce report during 2008 there were 2,709cases and 14 deaths (CFR: 0.52), in 2009 there were 2,190 cases and 2 deaths (CFR: 0.09) and in 2010there were 4,426 cases with 24 deaths (CFR: 0. 54) with 561,36 incidents per 100,000 population.South Denpasar District was one of areas with the highest dengue cases among other districts. Influence of knowledge factors, attitudes, behaviors eradication of mosquito breeding toward dengue infection is very important. The Purpose of this study is to know the relationship between the level of knowledge, attitude and behavior eradication of mosquito breeding place towards dengue infection in South Denpasar District. This study is an observational study with case-control pairs design. Case is new cases of dengueinfection and control is not suff ering from dengue infection by age, gender and origin of the sameresidence with the case. There were 150 samples of cases and controls studied. Data knowledge, attitudes, and PSN behavior were collected by interview and observation. There is a relationship between the level of knowledge, attitudes and behaviors. The level of knowledge value OR=2.72 (CI95% 1.365 to 5.424), Attitude value OR=4.28 (CI95% 2.159 to 8.497) PSN Behavioral value OR=3.41 (CI95% 1.240 to 7.692). There is a relationship between the level of knowledge, attitude and behavior eradication of mosquito breeding place towards dengue infection in South Denpasar District, Denpasar.